Принципи публічної служби: системно-діяльнісний вимір - Шовкун, Ю. І.; Shovkun, Yu. I. (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 2. - С. 83-95, 2024)
Запропоновано бачення системи принципів публічної служби, яка складається з таких блоків: міжнародні принципи публічної служби; принципи державного управління (організаційні, функціональні; цільові, акомодативні); правові принципи (загальні принципи права, принципи адміністративного права (відкритість і прозорість, гнучкість, дотримання прав і свобод людини, ефективність; заборона свавілля, інноваційність, компетентність, підзвітність і підконтрольність тощо); спеціальні принципи права, які регламентують проходження служби окремими категоріями публічних службовців.

A system of principles of public service has been formed, which consists of three principle blocks. 1. International principles of public service: supremacy of law; legality; effectiveness; objectivity; impartiality; justice; virtue; public activity regarding the management of state affairs, in particular those related to entry into public service, its completion and legislative support; balance of public and private interests when making decisions; transparency (passing public service and activities of public servants); responsibility of public servants to the population and the state for their professional activities; publicity, which involves the mandatory publication of open information about the work of public servants, etc. 2. Principles of public administration: a) organizational; b) functional; c) targeted; d) accommodative. 3. Legal principles: a) general principles of law (humanism, democracy, separation of powers into legislative, executive and judicial, legal certainty, presumption of innocence, proportionality, equality, legal responsibility; b) principles of administrative law (openness and transparency, flexibility, compliance human rights and freedoms, efficiency, prohibition of arbitrariness, innovation, competence, accountability and control, priority of laws of Ukraine and international documents regulating administrative and legal relations, social cohesion, stability and long-term orientation); c) special principles of law that regulate the passage of service by certain categories of public servants (equal access to public service, choice, patriotism, people's power, loyalty to constitutional duty and oath in case of taking it, state support, observance of official (executive) discipline and professional ethics, independence, failure to comply with illegal orders and instructions, consolidation of state and local interests, readiness for prompt performance of official tasks).

Предложено видение системы принципов публичной службы, состоящей из следующих блоков: международные принципы публичной службы; принципы государственного управления (организационные, функциональные; целевые, аккомодативные); правовые принципы (общие принципы права, принципы административного права (открытость и прозрачность, гибкость, соблюдение прав и свобод человека, эффективность; запрет произвола, инновационность, компетентность, подотчетность и подконтрольность и т.п.); специальные принципы права, регламентирующие прохождение службы отдельными категориями публичных служащих.
Principles of public service: system-activity dimension
Keywords: публічна служба; державна служба; принципи; засади; належне врядування; публічні службовці; морально-етичні принципи; public service; government service; principles; proper governance; public servants; moral and ethical principles; публичная служба; государственная служба; принципы; основы; надлежащее управление; публичные служащие; морально-этические принципы